Designing sustainable food experiences: Rethinking sustainable food tourism. (1st December 2020) - Leer, Jonatan
In this article, the position that there is a good case for sustainable food tourism despite the negative impact on the climate caused by tourism and travelling practices is argued. This requires, however, that we develop well-designed sustainable food experiences. We need to redesign and rethink the very idea of the food experience with particular focus on participation, the role of the consumer, the accessibility of the food design, and the potential of local contexts, to give some universal examples. This does not mean that sustainable food tourism is or can become carbon neutral. It means that the job of the food designer is to offer climate-friendly solutions and, maybe more importantly, that sustainable food experience designers should focus on how to inspire more sustainable food consumption and anti-consumerist lifestyles beyond the context of the experience. These arguments are presented via a case study of a sustainable food experience from the Faroe Islands.